Mitochondrial Myopathy in Follow-up of a Patient With Chronic Fatigue Syndrome - Fernando Galán AOPT; Isabel de Lavera PhD; David Cotán PhD; José A. Sánchez-Alcázar AOPT (SAGE Publishing, 2015)
Introduction . Symptoms of mitochondrial diseases and chronic fatigue syndrome (CFS) frequently overlap and can easily be mistaken. Methods . We report the case of a patient diagnosed with CFS and during follow-up was finally diagnosed with mitochondrial myopathy by histochemical study of muscle biopsy, spectrophotometric analysis of the complexes of the mitochondrial respiratory chain, and genetic studies. Results . The results revealed 3% fiber-ragged blue and a severe deficiency of complexes I and IV and several mtDNA variants. Mother, sisters, and nephews showed similar symptoms, which strongly suggests a possible maternal inheritance. The patient and his family responded to treatment with high doses of riboflavin and thiamine with a remarkable and sustained fatigue and muscle symptoms improvement. Conclusions . This case illustrates that initial symptoms of mitochondrial disease in adults can easily be mistaken with CFS, and in these patients a regular reassessment and monitoring of symptoms is recommended to reconfirm or change the diagnosis.